Application of 2D Electrical Resistivity Method and Ground Penetration Rader for Detection of the Archaeological Remains in Kish Site, Babylon, Iraq - Al-Rawi, Zubayda A.; Al-Banna, Ahmed Sh. (Iraqi Journal of Science, 2023)
The 2D electrical resistivity imaging (ERI) is a non-destructive method with good efficiency to detect shallow subsurface features. The archeological subsurface features were investigated with this method in most cases with the assistance of other methods such as GPR method. Eleven 2D ERI profiles were carried out to investigate the subsurface archeological features in the Kish site in the Babylon area. The 2D electrical resistivity survey was achieved with ABEM Terrameter-LS2 Device and 30 electrodes with 1-meter spacing between the adjacent electrodes along each profile. The length of the profile is 29 meters and the spacing between the adjacent profiles is 3 meters. The software RES2DINV was used to obtain the final inverted models. The resistivity value of the study site is low, not exceeding 10 ohm.m. The variation in the resistivity anomalies values indicates many possible buried walls on the site. The clearest anomaly, which shows relatively high resistivity at the distance range of 8-11 m, appeared in all profiles nearly at the same position and extended in depth from 0.25-4 meters. This anomaly is interpreted as an ancient wall. Profiles 1, 5, and 10 to check the resistivity result. The GPR survey result generally confirms the resistivity result. The 2D ERI and GPR methods successfully detect the buried wall in the study site.